Best Practices for Adult Educators Working in Cross-Generational Learning Spaces - Andrea Nikischer (Adult Education Research Conference, 2017)
This presentation will provide best practices for working with cross-generational groups of adult learners. The specific needs of Millennials, Generation X, Baby Boomers and Traditionalists will be addressed.
Keywords: cross-generational; millennials; best practices